Interference Reduction Consisting of Pre-Distortion Filtering with Selective Transmit Diversity - Silva, Mário Marques da (2015)
The purpose of the current paper is to analyze several schemes to combat both the MAI and fading, in the downlink direction. We propose a new pre-distortion (PD) filtering technique, which can be used to combat the Multiple Access Interference (MAI), combined the Selective Transmit Diversity (STD) for high data rate transmissions over frequency selective Rayleigh fading channels. The proposed PD scheme considers a Rake in the receiver. By pre-distorting the signals to be transmitted by the Base Station (BS) with a Minimum Variance (MV) algorithm, the orthogonality between the desired signal and all interfering signals can be improved. With the PD, the increase in performance is achieved with a small increase in power processing at the BS, avoiding any need to increase complexity at the Mobile Station (MS).